“The time has come for a new word”: Katherine Mansfield’s Literary Ethics - Alice BORREGO (E-REA)
This article examines how Katherine Mansfield’s literary ethics and aesthetics were challenged by the First World War. Mainly focusing on her non-fictional writings, it suggests that the conflict led Mansfield to develop and call for an ethical responsibility towards her entire generation – a disposition that finds its expression in her fragmented literary technique. Dwelling on what Stephen Ross calls a modernist “ethical impulse to improve upon the status quo”, this article aims at showing how the war progressively led Mansfield to draw a modernist manifesto that advocated a “new word”.